2007
DOI: 10.1002/ejoc.200601029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzofulvenes by Palladium‐Catalyzed Cyclization of 1,2‐Dialkynylbenzenes

Abstract: A palladium-catalyzed cyclization of enediynes for the synthesis of benzofulvenes 2 in yields of 59-76 % was accomplished by treatment of dialkynylbenzenes 1 with 5 mol-% of PdX 2 and 3 equiv. of CuX 2 in acetonitrile at 60°C for 2 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…[6] Recently, we found that treatment of 1,2-dialkynylbenzenes with five mol% of PdCl 2 and two equivalents of CuCl 2 gave benzofulvenes in good chemical yields. [7] Our continued interest in the cyclization reactions of enediynes for the synthesis of heterocycles [8] encouraged us to investigate the cyclization reaction of methyl 2-[6-substituted-3(Z)-hexen-1,5-diynyl]benzoates (1) in the presence of catalytic amount of PdCl 2 and three equivalents of CuCl 2 to give functionalized dibenzo-…”
mentioning
confidence: 99%
“…[6] Recently, we found that treatment of 1,2-dialkynylbenzenes with five mol% of PdCl 2 and two equivalents of CuCl 2 gave benzofulvenes in good chemical yields. [7] Our continued interest in the cyclization reactions of enediynes for the synthesis of heterocycles [8] encouraged us to investigate the cyclization reaction of methyl 2-[6-substituted-3(Z)-hexen-1,5-diynyl]benzoates (1) in the presence of catalytic amount of PdCl 2 and three equivalents of CuCl 2 to give functionalized dibenzo-…”
mentioning
confidence: 99%
“…Initially, we focused on the regioselective construction of the halogenated benzofulvenes 23. The halogenation reactions of benzofulvenes are mostly directed by using electrophilic halogenating agents, which have high oxidizing ability 24. Therefore, the advanced reactions using readily available halide anions directly should be undoubtedly easier to handle.…”
Section: Methodsmentioning
confidence: 99%
“…Alabugin and co‐workers have developed a two‐step strategy for the synthesis of benzofulvene by Bu 3 SnH‐mediated 5‐ exo ‐ dig radical cyclization of a diaryl enediyne. Subsequently, Lee et al . have explored the synthesis of benzofulvenes by Bergman cyclization using a Pd/Cu catalyst.…”
Section: Figurementioning
confidence: 99%